Integrated management of pigeon pea wilt using fungicide and bioagent - and C.D. MAYEE, R.M. GADE*, K.K. ZOTE (Indian Phytopathology, 2007)
The investigation was made to study management of pigeonpea wilt (Fusarium udum Butler). Soil solarization raised the soil temperature up to 54°C, 45.8 °C and 39.80 °C at 5, 10 and 15 cm depths, respectively. Susceptible variety ICP 2376 showed maximum wilting and it was 100 per cent in untreated check at 150 CAS. Soil solarization alone and its combination of seed treatment with thiram + benomyl 1:1@ 3g/Kg seed reduced wilting to the extent of 22.8,22.6% during Jirst year and 16.3and 15.7% during second year, respectively. Among bioagents seed treatment with Trichoderma harzianum @ 4 g/Kg seed had 52.7 and 52.1 % wilt incidence during first and second year, respectively. It was significantly lower than untreated control. The population of F. udum was drastically reduced immediately after solarization and the reduction was nearly complete in all solarized plots (0.3 cfu/20 mg soil), However, differences in seedling emergence were non significant in all treatments